2022
DOI: 10.1002/ehf2.13864
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and prognostic value of N‐terminal pro‐brain natriuretic peptide and high‐sensitivity C‐reactive protein in mildly dilated cardiomyopathy vs. dilated cardiomyopathy

Abstract: Aims Mildly dilated cardiomyopathy (MDCM) was characterized as a subset of dilated cardiomyopathy (DCM) with systolic dysfunction and modest ventricular dilatation, of which the prognostic studies were limited. We aimed to compare the prognostic value of the N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity C-reactive protein (hs-CRP) between MDCM and DCM. Methods and resultsWe retrospectively included hospitalized patients diagnosed with DCM and a left ventricular ejection fraction ≤ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…We report the rather unexpected finding that there are equal survival rates in both DCM and HNDC groups, along with comparable free-CV death survival, and event-free survival (including all-cause mortality, HTX, and LVAD implantation). To the best of our knowledge, there are only two studies focused on this issue with >100 patients: those by Feng et al [16] and Gigli et al [17]. Importantly, both authors did not even use the ESC-endorsed term of HNDC, but instead used “mildly dilated cardiomyopathy.” According to these studies, HNDC patients had a better prognosis than DCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report the rather unexpected finding that there are equal survival rates in both DCM and HNDC groups, along with comparable free-CV death survival, and event-free survival (including all-cause mortality, HTX, and LVAD implantation). To the best of our knowledge, there are only two studies focused on this issue with >100 patients: those by Feng et al [16] and Gigli et al [17]. Importantly, both authors did not even use the ESC-endorsed term of HNDC, but instead used “mildly dilated cardiomyopathy.” According to these studies, HNDC patients had a better prognosis than DCM.…”
Section: Discussionmentioning
confidence: 99%
“…[16] more than 30% did not receive renin-angiotensinaldosterone system inhibitors [16,17]. At present, it is very difficult to provide a clear explanation of this intriguing finding.…”
Section: Outcomes In Dcm and Hndcmentioning
confidence: 99%
“…The protective effect of higher SBP was consistent with previous studies [ 42 , 43 ], and the underlying mechanism may be that patients with higher SBP had better tissue perfusion and cardiac function. Meanwhile, NT-proBNP consistently presented prognostic value that cannot be ignored [ 44 ]. The negative effect of LVEDD in this study was not surprising, since it had been demonstrated that expansion of LVEDD increased the risk of HF and sudden cardiac death [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Univariate and multivariate Cox proportional hazards regression were used to evaluate the association of baseline remnant cholesterol levels with time to all-cause mortality. According to our previous studies and guidelines, the selected potential confounders in the multivariable analysis were sex, age, BMI, hypertension, diabetes mellitus, CAD, heart rate, SBP, DBP, hemoglobin, ALB, ALT, AST, TBIL, serum uric, eGFR, hsCRP, logNT-proBNP, LVEF, New York Heart Association (NYHA) Functional Class and pharmacotherapy ( 1 , 10 , 15 – 18 ). Smooth curve fitting with full adjustment of the covariates was employed to explore the dose–response relationship between remnant cholesterol and the risk of all-cause mortality.…”
Section: Methodsmentioning
confidence: 99%